URDU TRANSLATION OF 16-ITEM OF SCALE TO MEASURE PROSOCIAL BEHAVIOR IN ADULTS - Sheema Shahid; Noor-ul-Ain (International Journal of Contemporary Issues in Social Sciences, 2024)
The motive of the study is to translate the 16-item scale to measure Procosial behavior in Adults into Urdu and to establish the factorial structure and reliability of the scale. The procedure was executed in two phases. In the first step the back and forth translation method is used followed by the second step which is to demonstrate the psychometric property of the scale to establish the reliability and its validity. In the first phase the scale was translated back and forth whereas the second phase involves EFA and the subsequent CFA along with invariance measurement of test. The reliability estimate of the scale is 0.909. CFA exhibit the two factor goodness of fit indices for the scale. Two factor structure for the scale is displayed by EFA. The model fit values for the scale includes; the adjusted goodness-of fit index value: 0.893, goodness of fit index, value: 0.92, the incremental fit index value: 0.93, the comparative fit index value: 0.93 and the root mean square error of approximation (RMSEA) value: .071.The scale shows good attributes of internal reliability. The composite reliability and the convergent validity are the good measure of the scale.The Urdu version of the scale is an absolute measure of the level of prosocialness in Adults. A good positive relation has been observed between PSSA (Prosocialness Scale for Adults.) and PBSI(Prosocial Behavioral Intention Scale) through the analysis of criterion related validity.